Financial Performance Analysis of PT Bank Syariah Indonesia - Al Insani Mutiara Ramadhan; Wahyu Febri Ramadhan Sudirman; Hidayat Hidayat (Journal of Financial and Business, 2024)
This research aims to analyze the financial performance of PT Bank Syariah Indonesia (BSI) from 2022 to 2023 through evaluating main financial ratios. The data used includes current ratio, quick ratio, return on assets (ROA), return on equity (ROE), and capital adequacy ratio (CAR). Analysis is carried out to understand changes in bank financial conditions and their implications for stability and operational performance. the analysis results show a significant increase in short-term liquidity with an increase in the current ratio and quick ratio, which reflects better liquidity management. Increasing ROA and ROE indicate increased efficiency in the use of assets and equity to generate profits. In addition, the increase in CAR confirms that BSI has stronger capital reserves to face financial risks. These findings paint a positive picture of BSI's financial health and support investor and stakeholder confidence in the bank's future.